Teaching innovation n in geo-technological subjects: The experience of TIGame in the University of Cantabria (Spain) - De Cos-Guerra, Olga; Pérez-Díaz, Sebastián (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study is framed in the V and VI calls for teaching innovation projects of the Universidad de Cantabria (Spain). After incorporating gamification methods and short videos in teaching Geo-technologies, our results demonstrate the high degree of satisfaction of participating students in the innovation project, reaching an average of 4.45 over 5.0 and the competences and teaching goals of the subject were satisfactorily achieved. The experience is exportable to other teaching contexts without specific funding needs.